Upaya Perlindungan Lingkungan Sebagai Bagian dariPerlindungan Hak Asasi Manusia dalam Perspektif Hukum Positif - suryati; Teguh Anindito; Wiwin Mochtar Wiyono; Nurlaeli Sukesti Ariani Nasution (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2021)
The issue to be discussed is environmental protection efforts as part of the protection of human rights inIndonesian positive law. This writing uses normative research methods. The results of the analysis show thatthere are several government programs to protect the environment in Indonesia, for example, the NationalAction Plan for Human Rights, and the planting of a million trees. Legal instruments on environmentalprotection as part of the protection of Human Rights, which are based on national law as contained in the1945 Constitution, Law No. 32/2009, and Law No. 39/1999. Then based on international law, it is stated inPrinciple 1 of the Declaration. Stockholm 1972, and its Preamble. However, there is still a lot of damage orenvironmental problems caused by humans. Realizing how important the environment is as part of human rights,the community should be more concerned about protecting and respecting the environment for the sake ofsurvival. In order to minimize environmental problems, in addition to the existing regulations, strictersupervision and enforcement are also needed. Environmental protection in Indonesia needs to be furtherimproved so that the continuity of life is more guaranteed, because the right to a good environment is the right ofevery human being.